Age‐related change of auditory functional connectivity in Human Connectome Project data and tinnitus patients. Issue 1 (5th February 2020) - Minami, Shujiro B.; Oishi, Naoki; Watabe, Takahisa; Wasano, Koichiro; Ogawa, Kaoru
Abstract: Background: We reported that tinnitus patients showed reduced levels of auditory functional connectivity (FC) in comparison with normal hearing control subjects, and that we succeeded in objective diagnosis of tinnitus with 86% sensitivity and 74% specificity by focusing only on auditory‐related FC. However, the age‐related change of auditory FC is not clarified. In this study, we examine age‐related change of the auditory FC using the database of Human Connectome Project (HCP) and compared with our database of tinnitus patients. Method: From the HCP database HCP Lifespan Pilot project, we studied five age groups, 8 to 9 years old, 14 to 15, 25 to 35, 45 to 55, and 65 to 75. We also applied our tinnitus patients' resting‐state functional magnetic resonance imaging (fMRI) database, which is divided into three generations; 20 to 40 years old, 40 to 60, and 60 to 80 to compare with the HCP database. The resting state fMRI analyses were performed using the CONN toolbox version 18. As auditory‐related regions, Heschl's gyrus, planum temporale, planum polare, operculum, insular cortex, and superior temporal gyrus were set as the regions of interest from our previous reports. Result: Auditory FC is strongest among adolescents and reduces with age. But the auditory FC of tinnitus patients were significantly less than those of HCP data in each generation. Conclusion: Although auditory FC decreases with age, tinnitus patients have less auditory FC compared with age‐matched controls. The age‐matched cutoff values are necessary for an objective diagnosis of tinnitus with resting state fMRI.